REKONTRUSKSI PERAN AYAH DALAM PENDIDIKAN KELUARGA ANALISIS GENDER ISLAM TERHADAP KONSEP MADRASAH PERTAMA - Ulfa Arkhetafaza; Ardi Antoro; M. Zakian Ifada (LPPM STAI Muhammadiyah Probolinggo, 2026)
The family is the primary educational institution for children, playing a significant role in shaping their character and values. In Islam, the phrase “al-umm madrasatul ula” highlights the mother as the child's first school. This paradigm often places the mother as the main educator while the father is seen merely as a breadwinner. As a result, the father's role in family education receives less attention, even though his involvement is crucial for a child’s development. This study aims to reconstruct the father's role as an educator within the family from an Islamic gender perspective, emphasizing the equal responsibility between father and mother. The method used is a qualitative-interpretative literature study, analyzing classical and contemporary literature related to family education, parental roles, and gender perspectives in Islam. The findings indicate that Islam advocates for a fair and balanced division of parenting roles. The father, in addition to being the head of the family, is also responsible for educating, providing spiritual guidance, modeling good character, and meeting the emotional needs of children. The Islamic gender perspective emphasizes equality and justice in parental roles, making both the father and mother equally responsible as the child's